Triaxial extension tests on sandstone using a simple auxiliary apparatus. (August 2019) - Zeng, Bin; Huang, Da; Ye, Siqiao; Chen, Fuyong; Zhu, Tantan; Tu, Yiliang
Abstract: Tensile failure, hybrid failure (combined tension and shear) and shear failure are the three basic failure types of brittle rock. For a long time, little attention has been paid to the first two failure types except for the failure strength of direct/indirect tension, and the deformation characteristics and failure criterion of rock in triaxial extension (herein "triaxial extension" denotes axial tension/unloading-tension in confining pressure P c ) are still unclear. This paper proposes a simple auxiliary apparatus to implement triaxial extension tests of cylindrical rock specimens combined with a servo-controlled MTS machine. Subsequently, the mechanics behaviors of sandstone in triaxial extension tests under different constant confining pressures ( P c = 0, 5, 10, 15, 20, 30, 40, 50 and 60 MPa) are experimented and analyzed in detail, including the fracture angle, the failure surface morphology, the deformation and strength. With the increase of confining pressure, the failure type of sandstone presents a continuous transition from tensile failure to hybrid failure and to shear failure as a whole. The changes of failure morphology, elastic modulus, Poisson's ratio, maximum strain and failure strength with increase in P c show significant difference among three failure types. For the tested sandstone, the partitions of confining pressure between tensile failure and hybrid failure and between hybrid failure and shear failure are approximately at 20 MPa and 40 MPa, respectively. Hoek-Brown criterion with a tension cut-off and Fairhurst criterion are applicable to fitting the failure strength of triaxial extension test, and the latter presents a satisfying continuous transition from tensile failure to shear failure.